Ultimate alchemy - OSHO (Pune, 2000)
The Ultimate Alchemy: v. 1: Talks on the Atma Pooja Upanishad The unknown is the message of the Upanishads. The basic, the most foundational, always remains unknown; that which we know is always superficial. Osho observes that this Upanishad is one of the most beautiful and also one of the most neglected. He also points out that commentators usually are either on the path of love or the path of knowledge. But the commentator on this particular Upanishad is unique in being neither. Osho is perhaps the first person to discuss these sutras in such a way that the reader can feel a sense of oneness beyond the apparent contradictions. He talks on philosophy as a bridge between science and religion, different dimensions of listening, the role of doubt, the way to know whether one has transcended sex, the difference between projections and authentic feelings, and much more. He also explains how his words are a response to, not a commentary on these sutras.
Keywords: Meditation